Education as Moderator to Knowledge Consumers in Creating Awareness of Halal Food Consumption - Othman, Khatijah; Md Hamdani, Suhailiza; Sulaiman, Mashitah; Ramly, Roslizawati; Mutalib, Marina Munira (2018)
It is imperative for the Muslim to observe the consumption according to Islamic teaching based on the Quran and Sunnah and according to the Islamic Fiqh. Education in terms of basic Islamic rules in regards to the Muslim food is very important especially to create awareness in determine the Halalness of the food consumed. Hence this study focusses on education as moderator towards knowledge and awareness of the Muslim consumers over their consumption of Halal food product. Data were collected from 162 respondents on a random sampling basis. Quantitative analysis was conducted using SEM AMOS version 22 in determining education as moderator to knowledge and awareness of Muslim consumers. The finding shows that the level of the education plays a significant role as moderator in strengthening the knowledge of Muslim consumer in utilizing Halal food product. It indicates that knowledge is positively significant related to awareness. However, the relationship of understanding related to awareness is not significant maybe due to the attitude and practices of the Muslim consumer themselves. The study shows that consumers’ education moderates the relationship between knowledge and awareness. Hence the emphasis of relevance government sector and other Islamic institution to educate the society at large and Muslim consumers in specific is crucial as for them to get the benefit of education in increasing knowledge and awareness that comply with Shariah in food consumption